Price Discrimination Strategy of Low-Cost Airlines - Petrovic, Jelena; Petrović, Nikola (Industrija, 2015)
The main objective of this research was to determine whether the prices of airline tickets increase monotonically over time. The authors analyzed the market share of low-cost airlines during the period after the Serbian air transport deregulation of the lines connecting Belgrade to other worldwide destinations. In the observed period, Wizz Air achieved the highest increase in market share. This airline held a monopoly over all lines except the Belgrade-Rome line in the observed period. Based on the theorem on monotonic function, Spearman`s coefficient, and data on Wizz Air’s airfare changes for the Belgrade-Rome line, the results indicate a correlation between the time of ticket purchase and its price, but the prices of low-cost airline tickets do not monotonically increase over time.